(untitled) (ARQUISUR Revista, 2014)
The purpose of this research is to explore the usage of replicable and typological, yet alternative drainage structures that are able to solve the domestic drain problem within the limits of the private land in some preset suburban areas in the country. It uses the treatment, recycling and reuse of primary and grey water as a strategy for environmental security. It pretends to show finished examples of environmentally appropriate technical solutions to future users and to public authorities. These will prove themselves adequate for private users as a solution to the yet unsolved problems that we can find in the suburban and rural Uruguay.